Gear‐shifting control of non‐synchronizer electric‐driven mechanical transmission with active angle alignment. (7th October 2021) - Lu, Ziwang; Chen, Hongxu; Wang, Lijun; Zeng, Yuanfan; Ren, Xin; Li, Kailin; Tian, Guangyu
Abstract: Non‐synchronizer electric‐driven mechanical transmission (EMT) has advantages of low cost and simple mechanical structure, which is a key assembly in electric vehicles. In such an system, as the synchronizer is removed from the mechanical transmission, big impacts between the sleeve and clutch gear arise during a gear shift, which cause a long power‐off interruption. In this article, our contribution is to propose a novel control strategy to avoid impacts by achieving both zero relative rotational speed and angle differences between the sleeve and clutch gear. To obtain this strategy, we first derive the dynamic model of the gear‐shifting process as a hybrid automaton (HA) model. Based on the HA model, we can see that impacts can be eliminated when the rotational speed and angle differences become zeros. Then, to obtain zero rotational speed and angle differences and reduce the gear‐shifting time, a time‐optimal control law to synchronize the rotational speed and angle is first solved based on Pontryagin's minimum principle. Meanwhile, to resolve the solution difficulty brought by the period‐varied rotational angle difference, we introduce an optimal initial angle difference, and then use an incremental angle difference to replace the period‐varied one. Based on that, a model tracking strategy is proposed to enhance the system's antidisturbance capacity. For the gear‐shifting actuator, a dual bang‐bang control law is solved to save the gear‐shifting time. Finally, we carry out simulations and bench tests to validate the control strategy. Results show that the control strategy can indeed reduce impacts and power‐off time.